Subjective Oral Health in Dutch Adults - Gijsbert H.W. Verrips; Annemarie A. Schuller (Dentistry Journal, 2013)
Aim: To determine whether the subjective oral health (SOH) of the Dutch adult population was associated with clinical and demographic variables. Methods: A clinical examination was conducted in a sample of 1,018 people from the Dutch city of ‘s-Hertogenbosch. SOH was measured using the Dutch translation of the short form of the Oral Health Impact Profile (OHIP-NL14). Results: The average score on the OHIP-NL14 was 2.8 ± 5.9 and 51% of the respondents had a score of 0. Dental status was the most important predictor of SOH. Conclusions:  The SOH in the Dutch adult population was much better than in groups of adults in Australia, the United Kingdom and New Zealand. Nevertheless, there were important variations in SOH related to dental and socio-economic status.